Clean Shipping: Exploring the impact of emission regulation - Sari Repka; Johan Mellqvist; Tadeusz Borkowski; Jukka-Pekka Jalkanen; Jan Eiof Jonson; Lars Barregard; Eunice Olaniyi; Gunnar Klaus Prause; Michael Gauss; Jari Walden; Erik Svensson; Eugene Genikhovich; et al. (EnviSuM project, 2022)
The environmental impact of the maritime industry has been under much public discussion,
culminating in 2015 when regulations limiting sulphur content from shipping vessels came into
effect in the Baltic Sea. Since then, the maximum sulphur content of fuel used by all ships navigating the Sulphur Emission Control Area (SECA) must be no more than 0.1 per cent. Up-to-date information on the
technical efficiency and socio-economic impacts of different clean shipping solutions and their
capacity to comply with the regulations, however, is currently very limited. In order to develop future environmental regulations, policy makers and authorities need more knowledge. The shipping industry also needs to make informed investment decisions. To allow for knowledge-based decision making, discussions are needed involving maritime authorities, policy makers, NGOs, and the private sector.
We have answered questions on the shipping industry's compliance with environmental
regulations, examining the technical efficiencies of different techniques for removing pollution
from exhaust gases. We have also explored the cost-effectiveness of various compliance
measures used across the industry.
Modelling methods have enabled us to assess current and future compliance costs as well as
look at the effects on public health and the environment. We have taken a closer look at three
cities in the region to spread best practice on air quality measurement and modelling at a local
scale. We have provided analysis to make recommendations that will improve the welfare of the
people of the Baltic Sea Region. For environmental regulation to be effective, compliance needs to be monitored and noncompliance needs to be sanctioned. We have also presented findings on compliance levels and reflect on the attitudes of ship-owners responsible for meeting the regulations.
The project aims to support maritime businesses and economic growth. Clean shipping solutions
provide the potential for businesses to innovate. The development of clean shipping technologies
leads to spin-off enterprises and allows European industry actors to lead the way in global
markets. The Baltic Sea Region is a forerunner in this respect, acting as a living laboratory for
clean shipping. The effectiveness of SECA was analysed by comparing the costs and benefits of the regulation according to a framework presented in Lähteenmäki-Uutela et al. (2018). As part of this work, we
have developed a free web-based economic decision-making tool to help companies estimate investment costs and decide what investments to make to comply with SECA regulations.
In addition to promoting technological development and improving future regulation, we have
been active in sharing the results with the wider community. Finding ways to meet the increasing
demand for improved air quality will ultimately bring economic opportunities as well as wellbeing
for the people of the region.